Intensive care unit nurses’ experiences regarding withdrawal of treatment and end of life care - Hussein, Shenaz (My University, 2022)
Background: The withdrawal of treatment and End of Life Care (EOLC) in the intensive care setting is a process that often has many challenges. This process can cause the intensive care nurse involved in the process to have many conflicting feelings. These feelings can affect the nurse and the process both negatively and positively. It can cause emotional distress and frustration resulting in poor decision-making and poor communication. It can also cause a feeling of relief that the patient will suffer no more. On the other hand, prolonging death can lead to patient suffering or ending the life of a patient too soon can result in anxiety and selfblame. Aim: The aim of the study was to describe the ICU nurses’ experiences with regard to withdrawal of treatment and EOLC in the adult intensive care units of a university affiliated public hospital in Gauteng. Methods: A qualitative descriptive design was used in this study. Purposive sampling method was utilized to select the sample of 15 (n=15) registered nurses working in the four ICUs of an academic hospital in the Gauteng province. In - depth semi- structured interviews were used to collect data. Braun and Clarke’s thematic analysis approach was utilized to analyse the transcribed interviews. Results: Three broad themes emerged from the study. These included obstacles to withdrawal of treatment and EOLC, emotional burden and coping mechanisms. Conclusion: For more than three decades ICU nurses face many challenges within the working environment while providing care to the dying patients and supporting their family members. It was evident from literature as well as from the study’s findings several obstacles concerning withdrawal of treatment and EOLC exist. These concerns are related to inadequate training for nurses, lack or inadequate support systems for nurses, the unfavourable nature of the ICU, nurses’ lack of or inconsistent involvement in decision-making, lack of communication and teamwork among the ICU team members. Despite the multi-cultural and diversified societies, and differences in EOLC practices globally, all ICU nurses experience similar obstacles to EOLC.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Science in Nursing to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, 2022